Community Learning Center (CLC) Management in Indonesia-Malaysia Border Area on Education for Sustainable Development (ESD - Wahyudin, Uyu; Hufad, Achmad; Hufad, Purnomo; Yunus, Dadang (International Journal of Psychosocial Rehabilitation, 2020)
--Education in Indonesian Border Area is one of the studies about education equity in Indonesia. Indonesian Consul General provided Community Learning Center (CLC) to fulfil the needs of compulsory education for Indonesian Workers’ children in Sabah Malaysia. This study will examine about the management analysis of CLC in border area to facilitate education access for Indonesian workers’ children in Malaysian schools. This study applied qualitative analysis and descriptive method. CLC as an institution manages programs started from the identification of learning needs, identification of potential sources, formulating the programs, planning the learning activities, implementation of the learning activities, supervision, and evaluation.